Biodegradation of Polyhydroxybutyrate, Polylactide, and Their Blends by Microorganisms, Including Antarctic Species: Insights from Weight Loss, XRD, and Thermal Studies - Volodymyr Skorokhoda; Ihor Semeniuk; Taras Peretyatko; Viktoria Kochubei; Oleksandr Ivanukh; Yuriy Melnyk; Yurij Stetsyshyn (Polymers, 2025)
This study explores the biodegradation of polyhydroxybutyrate (PHB), polylactide (PLA), and their blends by 11 bacterial species (including Antarctic strains) and 6 fungal species. Aeration significantly enhanced PHB degradation by mold fungi (Aspergillus oryzae, Penicillium chrysogenum) and bacteria (Paenibacillus tundrae, Bacillus mycoides), while Aspergillus awamori was most effective under non-aerated conditions. For PLA, degradation peaked under aeration with Penicillium chrysogenum and Bacillus subtilis. PHB/PLA blends degraded slower overall, with maximum degradation under aeration by Penicillium chrysogenum, Pseudoarthrobacter sp., and Flavobacterium sp. Biodegradation was assessed via weight-loss measurements, X-ray diffraction (XRD), and thermal analysis. PHB samples showed reduced crystallinity and thermal stability linked to weight loss, while PLA samples exhibited varied changes, often with increased crystallinity and stability depending on the microorganism. PHB/PLA blends displayed variable crystallinity changes, generally decreasing under microbial action. The search for effective plastic-degrading microorganisms, particularly from extreme environments like Antarctica, is vital for addressing plastic pollution and advancing sustainable polymer degradation.